Shaping a research agenda to ensure a successful European health technology assessment: Insights generated during the inaugural convention of the European Access Academy - Elaine Julian; Mira Pavlovic; Oriol de Sola-Morales; Fabrizio Gianfrate; Mondher Toumi; Heiner C. C. Bucher; Christian Dierks; Wolfgang Greiner; Peter Mol; Jean-François Bergmann; Tomas Salmonson; Ansgar Hebborn; et al. (Health Economics Review, 2022)
Objectives: Key challenges for a joint European Health Technology Assessment (HTA) include consolidated approaches towards the choice of adequate comparator(s), selection of endpoints that are relevant to patients with a given disease, dealing with remaining uncertainties as well as transparent and consistent management of related processes. We aimed to further crystallize related core domains within these four areas that warrant further research and scrutiny. Methods: Building on the outcomes of a previously conducted questionnaire survey, four key areas, processes, uncertainty, comparator choice and endpoint selection, were identifed. At the inaugural convention of the European Access Academy dedicated working groups were established defning and prioritizing core domains for each of the four areas. The working groups consisted of~10 participants each, representing all relevant stakeholder groups (patients/ clinicians/ regulators/ HTA & payers/ academia/ industry). Story books identifying the work assignments were shared in advance. Two leads and one note taker per working group facilitated the process. All rankings were conducted on an ordinal Likert Response Scale scoring from 1 (low priority) to 7 (high priority). Results: Identifed key domains include for processes: i) address (resource-) challenge of multiple PICOs (Patient/ Intervention/ Comparator/ Outcomes), ii) time and capacity challenges, iii) integrating all involved stakeholders, iv) conficts and aligning between diferent multi-national stakeholders, v) interaction with health technology developer; for uncertainty: i) early and inclusive collaboration, ii) agreement on feasibility of RCT and acceptance of uncertainty, iii) alignment on closing evidence gaps, iv) capacity gaps; for comparator choice: i) criteria for the choice of compara- tor in an increasingly fragmented treatment landscape, ii) reasonable number of comparators in PICOs, iii) shape Early Advice so that comparator fulfls both regulatory and HTA needs, iv) acceptability of Indirect Treatment Comparisons (ITC), v) ensure broad stakeholder involvement in comparator selection; for endpoint selection: i) approaching new endpoints; ii) patient preferences on endpoints; iii) position of HTA and other stakeholders; iv) long-term generation and secondary use of data; v) endpoint challenges in RCTs. Conclusions: The implementation of a joint European HTA assessment is a unique opportunity for a stronger Euro- pean Health Union. We identifed 19 domains related to the four key areas, processes, uncertainty, comparator choice and endpoint selection that urgently need to be addressed for this regulation to become a success.
Keywords: 330; EU HTA; Uncertainty; Comparators; Endpoints; Process; Clinical Trial Design; Patient-relevance; Access